PODCAST MARKETING: MODERN STRATEGIES FOR PROMOTING BUSINESS THROUGH AUDIO FORMAT - Bilyk, I. I.; Kolisnyk, V. S. (The actual problems of regional economy development, 2024)
The article explores current trends in the world of podcasting, particularly its use as an effective marketing tool. It conducts an analysis of contemporary trends in podcast marketing and highlights its advantages. The current state and prospects of podcast marketing are analyzed, identifying its main trends, as well as discussing the advantages and challenges of this tool for businesses. Research methods are based on the analysis of statistical data, a literature review, and online resources regarding popular genres, demand, development trends, and successful podcast marketing campaigns. The prospects of branded podcasts as an effective tool for promoting products, services, and company ideas are illuminated. It is noted that podcasts, due to their ability to reach target audiences with high precision, are becoming a key part of content marketing strategies. Examples of the most popular branded podcasts are presented, and the reasons for their success are examined. Information is provided on the advantages and challenges of podcast marketing for businesses, as well as strategies that include placing podcasts in popular directories, obtaining positive reviews and ratings, active use of social media, collaboration with influencers, and inviting guests. The importance of developing landing pages to enhance user convenience and effectively promote podcasts is emphasized. The research results indicate a rapid growth in the popularity of podcasts, their increasing importance in the field of marketing, and the expected further growth of this market. The main strategies and directions for the development of podcast marketing that can be beneficial for businesses are highlighted. The scientific novelty lies in the systematization and analysis of the latest data and trends in the field of podcast marketing, as well as in identifying the potential of this tool for business development. The research results can be useful for brands and marketers in formulating effective podcast marketing strategies to attract the attention of target audiences and increase their competitiveness in the market.